Implementasi Fault Tolerant System menggunakan Self-purging Redundancy pada Sistem Monitoring Suhu Ruang Server - Alfan Rafi'uddin Ardhani; Agung Setia Budi; Fitri Utaminingrum (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Server is a computer system that serves and controls access to clients that connected to it. Server is generally placed in a special room equipped with air conditioning. This is done to keep the temperature of server's components that generate heat when working. Server that work at high temperatures may cause a decrease in performance and if left unchecked can cause server outages and damages to its components. In several studies that have been done, the application of fault tolerant system is rarely used where the system only relies on a single sensor to obtain temperature data so it is susceptible to fault. Therefore, in this study, the self-purging redundancy method is used to determine the effect of the method on system's fault handling. In this research, 3 redundant modules are used in the form of Arduino Nano and temperature sensor DHT-22 to obtain temperature data which is then sent to a voter in the form of Arduino Uno. From this study, it is found that self-purging redundancy method has an effect on system's fault handling, where the system can tolerate error that occur in one redundant module at one time. In addition, the system has an accuracy of 85% and an average computation time of 14,8 milliseconds.